More than memory - Garlock, Dorothy (New York Warner Books, 2001)
Eight years have passed since their passionate young love went wrong. Now Nelda returns to her Iowa farmland home, only to rediscover her teenage love who was, for a few brief months, her husband. But is their love reawakening?
85179
Keywords: Love stories